Expanding the Scope of Functionalized Small Nonprotein Components for Holoabzyme 27C1. Issue 32 (27th August 2018) - Ishikawa, Fumihiro; Shirahashi, Masato; Hayakawa, Hiroshi; Tanabe, Genzoh; Tsumuraya, Takeshi; Fujii, Ikuo
Abstract: The creation of artificial enzymes that achieve high selectivity, and turnovers equivalent to natural enzymes remains a challenging aspect of biocatalyst research. The design of new catalytic proteins presents a straightforward test of our understanding of enzyme catalysis. The holoabzyme 27C1 possesses binding pockets for substrates, as well as for a large variety of functionalized small nonprotein components. Site‐directed chemical mutations have optimized the β ‐elimination activity of antibody 27C1, resulting in a 10 6 fold rate enhancement. In this study, we incorporate synthetic catalytic components with different steric properties into the binding site, and investigate the substrate scope of the 27C1‐catalyzed β ‐elimination reaction. Our results indicate that the flexibility and tunability of the binding pocket toward synthetic small molecules may enable incorporation of newly devised components, and thus, introduce novel reactivities. Abstract : Tunable pockets: Using site‐directed chemical mutations, we investigated the substrate scope of binding site for functionalized small nonprotein components. Antibody 27C1 exhibited flexible recognition properties toward synthetic co‐factors. Abzyme engineering using synthetic components provides a profound understanding of enzyme functions, opening new avenue in re‐engineering of existing enzymes and creating artificial protein catalysts.